Integrated assessment of social and environmental sustainability dynamics in the Ganges-Brahmaputra-Meghna delta, Bangladesh. (20th December 2016) - Nicholls, R.J.; Hutton, C.W.; Lázár, A.N.; Allan, A.; Adger, W.N.; Adams, H.; Wolf, J.; Rahman, M.; Salehin, M.
Abstract: Deltas provide diverse ecosystem services and benefits for their populations. At the same time, deltas are also recognised as one of the most vulnerable coastal environments, with a range of drivers operating at multiple scales, from global climate change and sea-level rise to deltaic-scale subsidence and land cover change. These drivers threaten these ecosystem services, which often provide livelihoods for the poorest communities in these regions. The imperative to maintain ecosystem services presents a development challenge: how to develop deltaic areas in ways that are sustainable and benefit all residents including the most vulnerable. Here we present an integrated framework to analyse changing ecosystem services in deltas and the implications for human well-being, focussing in particular on the provisioning ecosystem services of agriculture, inland and offshore capture fisheries, aquaculture and mangroves that directly support livelihoods. The framework is applied to the world's most populated delta, the Ganges-Brahmaputra-Meghna Delta within Bangladesh. The framework adopts a systemic perspective to represent the principal biophysical and socio-ecological components and their interaction. A range of methods are integrated within a quantitative framework, including biophysical and socio-economic modelling and analyses of governance through scenario development. The approach is iterative, with learning both within the project team and with national policy-making stakeholders. The analysis is used to explore physical and social outcomes for the delta under different scenarios and policy choices. We consider how the approach is transferable to other deltas and potentially other coastal areas.